“La actividad física en el rendimiento académico de los niños y niñas del Séptimo Año de Educación General Básica de la Unidad Educativa Miguel Ángel León Pontón del Cantón Riobamba Provincia de Chimborazo en el período febrero 2016 – junio 2016”. - Carrillo Álvarez, Víctor Hugo (2016)
The research called "PHYSICAL ACTIVITY IN CHILDREN´S ACADEMIC PERFORMANCE OF THE SEVENTH YEAR OF GENERAL BASIC EDUCATION FROM MIGUEL ANGEL LEON PONTON EDUCATIONAL UNIT IN RIOBAMBA CANTON CHIMBORAZO PROVINCE DURING THE PERIOD OF FEBRUARY - JUNE 2016" its general objective is to determine the influence of the practice of Physical Activity in children´s Academic Performance of the seventh year of Basic General Education from Miguel Angel Leon Pontón Educational Unit In Riobamba Canton Chimborazo Province, the participant shown in research was 68 students divided into 2 groups of 34 so-called control and experimental, the first work under the common methodology planned as the educational curriculum, and the experimental group under the proposed methodology in the manual physical, sporting and recreational activity. The research was quantitative and the grades of the first and second partial were used as a measuring instrument of the academic performance. The controlled group in the period before the investigation presented an average of RA of 8,46 / 10, T-AFC which is mandatory for all was 275 minutes per week, the T-AFEC was 37,9 minutes per week and T-CDPD was 22,1 minutes per week. The group presented an average of 8,29 RA / 10, T-AFC which is mandatory for all was 275 minutes per week, the T-AFEC was 41,5 minutes per week and the T-CDPD was 22,9 minutes a week, showing that the characteristics between the two groups had no difference at the beginning of the investigation. The control group was not subjected to any intervention and its results had no variation in relation to the experimental group which increased its results after statistical analysis to determine the value of P in both the GC and the GE between periods AI and DI, it was observed that the GC P is at a level ≥0,05 which means that the results are not significant, while the GE P was found at a level ≤0,001 determining that the results are highly significant, giving veracity to the research and demonstrating that the proposed intervention was effective.